The Effect Of Accounting Training And Business Experience On The Development Of Msmes In Pematang Siantar City - Wico Jontarudi Tarigan; Mahaitin H Sinaga; Djuli Sjafei Purba (Program Studi Akuntansi Universitas Simalungun, 2024)
Micro, small and medium enterprises in the Indonesian economy have a strategic role in building national economic productivity. The purpose of this study is to determine the effect of accounting training and business experience on the performance of MSMEs in Pematang Siantar City. The research method is to use quantitative methods with a descriptive approach. Data collection is carried out through surveys by distributing questionnaires to respondents. And the author did a measurement scale, which is measured using the Likert scale. The study population was all MSMEs in the city of Pematang Siantar and the sample consisted of 100 MSMEs. The hypothesis was tested with a coefficient of determination, F test and T Test using SPSS ver.25. The results showed that accounting training had a positive and significant effect on MSME performance and business experience had a positive and significant effect on MSME performance. This means that accounting training and business experience are very important in improving the performance of MSMEs